Cytosolic and Nuclear Co-localization of Betalain Biosynthetic Enzymes in Tobacco Suggests that Betalains Are Synthesized in the Cytoplasm and/or Nucleus of Betalainic Plant Cells - Chen, Ning; Yu, Zhi-Hai; Xiao, Xing-Guo (Frontiers in Plant Science, 2017)
Betalains replace anthocyanins as color pigments in most families of Caryophyllales. Unlike anthocyanins, betalains are derived from tyrosine via three enzymatic steps: hydroxylation of L-tyrosine to L-3,4-dihydroxyphenylalanine (L-DOPA; step 1), and conversion of L-DOPA to betalamic acid (step 2), and to cyclo-DOPA (cDOPA; step 3). The principal enzymes responsible for these reactions have been elucidated at the molecular level, but their subcellular localizations have not been explored; hence, the intracellular compartments wherein betalains are biosynthesized remain unknown. Here, we report on the subcellular localization of these principal enzymes. Bioinformatic predictors and N- and C-terminal GFP tagging in transgenic tobacco, showed that Beta vulgaris CYP76AD1 which mediates both step 1 and step 3, DODA1 that catalyzes step 2, and CYP76AD6 which also mediates step 1, were similarly localized to the cytoplasm and nucleus (although the P450s were also weakly present in the endoplasmic reticulum). These two compartments were also the principal locations of Mirabilis jalapa cDOPA5GT. The cytoplasmic and nuclear co-localization of these key enzymes in tobacco suggests that betalains are biosynthesized in the cytoplasm and/or nucleus of betalain-containing plant cells. Elucidation of the subcellular compartmentation of betalain biosynthesis will facilitate the bioengineering of the betalain biosynthetic pathway in non-betalain-containing plants.